ANALISIS KANDUNGAN VITAMIN C DAN β- KAROTEN DALAM DAUN KELOR (Moringa oleifra Lam.) DENGAN METODE SPEKTROFOTOMETRI UV–VIS - Masdiana Tahir; Nurul Hikmah; Rahmawati Rahmawati (Faculty of Pharmacy, Universitas Muslim Indonesia, 2016)
This research aimed to analyze the levels of vitamin C and β-carotene in Moringa leaves extract (Moringa oleifera Lam.) using UV-Vis spectrophotometry. Vitamin C on Moringa leaves are extracted with ethanol 96%. The extracts obtained was qualitatively analyzed of levels of vitamin C using specific reagents an iodine 1% and ammonium molybdate 5%. Than quantitatively using UV-Vis spectrophotometry at wavelength of 570 nm, obtained an verage grade of 7,96 mg/g. For β-carotene, Moringa leaves were extracted with acetone. The extract obtained was extracted again with ether, then saponified with KHO solvent 15% w/v in methanol, allowed to stand overnight. The extract obtained was extracted again with ether, then freed from wet with distilled water. Extracts were analyzed qualitatively using thin layer chromatography and quantitatively using UV-Vis spectrophotometry at wavelength of 450 nm and obtained an average grade of 3,31 mg/g.